Pendampingan Public Speaking Berbasis 3P (Preparation, Point, Performance) untuk Meningkatkan Kepercayaan Diri Siswa Madrasah Aliyah - Novi Ariyanti; Nuke Ladyna Anggerawati (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2026)
Public communication proficiency is a pivotal competency in the digital era; however, many madrasah students remain constrained by communication apprehension. This community service program aims to enhance students' self-confidence and oratory skills at MA Miftahul Falah through the 3P model (Preparation, Point, Performance). Utilizing Participatory Action Research (PAR), the initiative provided intensive training and clinical mentoring for 30 student leaders from January to February 2026. The results demonstrate a significant transformation: students' self-confidence increased by 70%, systematic messaging ability reached 70%, and technical performance mastery (vocal and gesture) surged to 75%. As a concrete output, the program produced a manual titled "Speak Up & Stand Out: Jago Public Speaking Tanpa Grogi" for independent practice. Overall, the 3P model serves as an integrative solution to cultivate young orators who are confident, digitally savvy, and grounded in the values of akhlakul karimah.